Pengaruh Stres Kerja terhadap Produktivitas Kerja - Andre Syahrul Subhana Kusmana; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
Abstract. This research was conducted on extension workers of the Ministry of Religion in the district II in Bandung. After the authors conducted a pre-survey by distributing questionnaires and interviews about work stress on work productivity, the results of the interviews could be concluded that the extension workers felt the uncertainty of information technology, boredom, lack of information technology skills, work demands, and family factors resulted in stress at work, although Extension workers are still working but if the work stress is prolonged, it will result in reduced productivity at work. This study aims to find out how work stress is when WFH is in the Covid-19 situation for extension workers at the Ministry of Religion in Bandung, how is work productivity during WFH in a Covid-19 situation for extension workers at the Ministry for Religion in Bandung, and whether there is an effect of work stress on work productivity during WFH during the Covid-19 situation. 19 extension workers from the Ministry of Religion in Bandung. This study uses descriptive and verification methods, using a quantitative research approach and operating the calculations using the IBMSPSS 25.0 program. Collecting data obtained through questionnaires, observations, interviews, and literature studies. The sampling technique is saturated sampling. Respondents in this study were extension workers of the Ministry of Religion for Regional Elections II Bandung City. The results of this study conclude that: 1) Work Stress (X) of the extension workers during WFH in the Covid-19 situation is in the High Category. 2) Work Productivity (Y) of the extension workers during the Covid-19 WFH situation is included in the Enough Category. (3) Job stress (X1) partially has a significant effect on Work Productivity (Y). Abstrak. Penelitian ini dilakukan pada penyuluh Kementerian Agama di Kecamatan II Kota Bandung. Setelah penulis melakukan pra survei dengan menyebarkan kuesioner dan wawancara tentang stres kerja terhadap produktivitas kerja, hasil wawancara dapat disimpulkan bahwa penyuluh merasakan ketidakpastian teknologi informasi, kebosanan, kurangnya keterampilan teknologi informasi, tuntutan kerja, dan faktor keluarga mengakibatkan stres dalam bekerja, walaupun penyuluh tetap bekerja namun jika stres kerja berkepanjangan maka akan mengakibatkan turunnya produktivitas dalam bekerja. Penelitian ini bertujuan untuk mengetahui bagaimana stres kerja saat WFH dalam situasi Covid-19 pada penyuluh di Kementerian Agama Kota Bandung, bagaimana produktivitas kerja selama WFH dalam situasi Covid-19 pada penyuluh di Kementerian Agama. di Bandung, dan apakah ada pengaruh stres kerja terhadap produktivitas kerja selama WFH selama situasi Covid-19. 19 penyuluh dari Kementerian Agama di Bandung. Penelitian ini menggunakan metode deskriptif dan verifikatif, dengan menggunakan pendekatan penelitian kuantitatif dan pengoperasian perhitungan menggunakan program IBMSPSS 25.0. Pengumpulan data diperoleh melalui angket, observasi, wawancara, dan studi kepustakaan. Teknik pengambilan sampel adalah sampling jenuh. Responden dalam penelitian ini adalah penyuluh Kementerian Agama Pilkada II Kota Bandung. Hasil penelitian ini menyimpulkan bahwa: 1) Stres Kerja (X) penyuluh pada saat WFH dalam situasi Covid-19 berada pada Kategori Tinggi. 2) Produktivitas Kerja (Y) penyuluh selama situasi WFH Covid-19 termasuk dalam Kategori Cukup. (3) Stres kerja (X1) secara parsial berpengaruh signifikan terhadap Produktivitas Kerja (Y).